MODERN MONETARY UNREST: PUBLIC POLICY RESPONSES TO THE ADOPTION OF BITCOIN AS A HEDGE AGAINST SYSTEMIC FIAT INFLATION - Mu'awwanah, Uliyatul; Mursidah, Mursidah; Masithoh, Fitria Nur; Mu'awanah, Mu'awanah; Hamdi, Muhammad (International Conference on Humanity Education and Society (ICHES), 2025)
The post-2008 crisis era, accelerated by the COVID-19 pandemic, has ushered in a permissive global monetary policy, raising essential questions about the sustainability of the fiat monetary system. This has triggered a trust deficit, fundamentally challenging what is termed the "Monetary Social Contract"-an implicit agreement wherein citizens entrust the store of value function to state-issued currency, with the adoption of Bitcoin in Indonesia becoming an expression of this unrest. This paper aims to (1) analyze the primary drivers behind the search for independent (non-state) hedge assets, (2) examine their implications for national monetary sovereignty, and (3) formulate a framework for innovative public policy responses using a qualitative approach through conceptual analysis and a literature study of secondary data. The findings indicate that the impetus for Bitcoin adoption originates not only from domestic inflation data but also as a reaction to the global phenomenon of systemic fiat devaluation. Its primary implications are the potential weakening of monetary policy transmission and a decline in the demand base for the Rupiah. It is concluded that prohibitive policy responses would be counter-productive. This paper recommends a dual-track approach: (1) strengthening the monetary social contract through innovation in state financial instruments, and (2) integrating independent (non-state) assets into a safe and controlled regulatory framework.